2005
DOI: 10.7202/706058ar
|View full text |Cite
|
Sign up to set email alerts
|

Weed survey of spring cereals in New Brunswick

Abstract: During 1986 and 1987, a weed survey of 187 New Brunswick cereal fields was conducted. A total of 76 species were identified of which 40 were considered agronomically important. About 50% of the species were perennial. Hemp-nettle (Galeopsis tetrahit), quack grass (Agropyron repens), sheep sorrel (Rumex acetosella), ox-eye daisy (Chrysanthemum leucanthemum), corn spurry (Spergula arvensis), and chickweed (Stellaria média) had the highest relative abundance values. Quack grass and hemp-nettle had the highest den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…It is common in southern areas of British Columbia, Ontario and Quebec and in the Maritime Provinces. In a weed survey of spring cereals in New Brunswick conducted in the late 1980s, L. vulgare occurred in 54% of fields surveyed and ranked fourth in terms of relative abundance (Thomas et al 1994). Frick et al (1990), surveying weeds in southwestern Ontario under different tillage regimes, found ox-eye daisy at low frequencies in soybean fields under conventional tillage (1.4% frequency).…”
Section: Geographical Distributionmentioning
confidence: 99%
“…It is common in southern areas of British Columbia, Ontario and Quebec and in the Maritime Provinces. In a weed survey of spring cereals in New Brunswick conducted in the late 1980s, L. vulgare occurred in 54% of fields surveyed and ranked fourth in terms of relative abundance (Thomas et al 1994). Frick et al (1990), surveying weeds in southwestern Ontario under different tillage regimes, found ox-eye daisy at low frequencies in soybean fields under conventional tillage (1.4% frequency).…”
Section: Geographical Distributionmentioning
confidence: 99%
“…Several studies have shown that some herbicides can have initial phytotoxic effects, although seedlings usually recover without severe damage, and yield loss are not observed (Díaz et al 1992;Ivany et al 2002;Thomas et al 1994;Tonks et al 1991;Volenberg et al 2002;Young et al 2003). In other studies, however, various clover species were exposed and evaluated for tolerance to different herbicides including pendimethalin and metolachlor (Tharp and Kells 2000), bentazon and 2,4-D (Evers et al 1993), 2,4-D and dicamba (Griffin et al 1984), and MCPA and 2,4-DB (Conrad and Stritzke 1980); in all cases, yield and persistence of the legume were markedly reduced.…”
Section: Introductionmentioning
confidence: 99%
“…(Fyles 1989). In New Brunswick, it is associated with understory plant communities of jack pine mixed hardwood forests (MacLean and Wein 1977), and as a common weed of cereal crops (Thomas et al 1994). Rumex acetosella is also commonly associated with lowbush blueberry fields in New Brunswick, Nova Scotia (McCully et al 1991;Jensen and Yarborough 2004), and Newfoundland (Penney et al 2008).…”
Section: Habitatmentioning
confidence: 98%